ما هية الشهادة في المسائل الشرعية والقانونية - محمود, عمر جمعة; البرزنجي, صباح محمد نجيب (Sulaimani Journal for Humanities, 2021)
That the certificate was and remains one of the most important means of proof, was standing, user-friendly efforts, as they have high, great and the rank in the Islamic Sharia And the importance of the certificate as the most important evidence upon which the judges in their judgments. came this study to deal with the certificate research and discussion, And that through an introduction and three sections. Where I dealt with in the first topic: the concept of testimony as evidence of proof and that through two requirements, and in it I explained in the first requirement: the definition of testimony in the language, and in the second requirement: the definition of testimony idiomatically. The second topic deals with the authenticity of testimony and its characteristics in Islamic jurisprudence and law through two requirements: the first requirement, in which the authenticity of the testimony was explained in Islamic jurisprudence, and in the second requirement, the authenticityof the testimony in the law was explained. 5And in the third topic, I dealt with the elements of testimony as legal and legal evidence, and conditions for taking them, and that through two requirements as well: The first requirement: the elements of the testimony were mentioned as evidence for civil proof. And the second requirement: the conditions of the witness are mentioned in civil evidence These issues were compared in light of the provisions of Islamic Sharia and the law, and finally it was concluded with the conclusion.